Analisis Penerapan Prinsip Good Governance Dalam Pengelolaan Sampah Di Kecamatan Tuah Madani - Rino Harbowo (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2024)
The people of Tuah Madani District have very little participation in waste management, namely in sorting waste between organic and non-organic waste, this is what makes waste management take so long. The aim of this research is to find out the implementation of Good Governance in waste management in Tuah Madani District and the factors -factors that influence the implementation of Good Governance. The research conducted used qualitative research to produce discoveries that would not have been possible to achieve. The types and sources of data used are primary and secondary data. This research uses observation, interview and documentation data collection techniques. Determining informants in this research used purposive sampling or purposive sampling techniques. The results of the research are that the implementation of Good Governance principles in waste management in the Tuah Madani sub-district is not optimal, there is a lack of creating a special website for conveying criticism and suggestions, there is a lack of open government information in resolving waste management problems for the community, such as a lack of TPS in each place. Factors that hinder the implementation of Good Governance principles in waste management in Tuah Madani sub-district are: lack of infrastructure for waste management, poor communication between the government and the community in resolving waste management problems